Etiology and Morphogenesis of Congenital Heart Disease From Gene Function and Cellular Interaction to Morphology - Nakanishi, Toshio; Markwald, Roger R.; Baldwin, H.Scott; Keller, Bradley B.; Srivastava, Deepak; Yamagishi, Hiroyuki (Springer Japan : Imprint: Springer, 2016)
This volume focuses on the etiology and morphogenesis of congenital heart diseases. It reviews in detail the early development and differentiation of the heart, and later morphologic events of the cardiovascular system, covering a wide range of topics such as gene functions, growth factors, transcription factors and cellular interactions that are implicated in cardiac morphogenesis and congenital heart disease. This book also presents recent advances in stem cell and cell sheet tissue engineering technologies which have the potential to provide novel in vitro disease models and to generate regenerative paradigms for cardiac repair and regeneration. This is the ideal resource for physician scientists and investigators looking for updates on recent investigations on the origins of congenital heart disease and potential future therapies.